Native collagen type II and Aflapin® in the management of hip and knee osteoarthritis: a single-centre prospective observational study - Maheshwari, Vaibhav; Daftary, Gautam V.; Patil, Nikita N.; Khemnar, Bhushan M. (International Journal of Research in Medical Sciences, 2026)
Background: Osteoarthritis (OA) affects over 595 million people worldwide, with cases rising by 132% from 1990. Standard NSAID therapy offers only symptomatic relief and has safety limits, driving interest in alternatives. Native type II collagen and Aflapin provide complementary immunomodulatory and anti-inflammatory effects. This study evaluates their combined efficacy and safety in hip or knee OA over 12 weeks. Methods: Adults (≥40 years) with confirmed hip or knee OA receiving native collagen type II 40 mg + Aflapin 100 mg as routine treatment were enrolled after consent. Key exclusions were recent corticosteroid/NSAID or intra-articular therapy, major comorbidities, obesity, pregnancy, or any other investigational drug use. Efficacy and safety were assessed via 100 mm VAS for pain and stiffness and a 5-point Likert scale for global OA status at weeks 4 and 12. Results: A total of 100 subjects (mean age 58.6 years; 57% female) were enrolled. Significant improvements in pain, stiffness, and overall OA status were observed by weeks 4 and week 12, with all subjects reporting pain relief and 99% showing reduced stiffness by week 12. No rescue medication was needed, and three minor adverse events (AEs) (headache, bloating, mild gastritis) resolved without treatment. Conclusions: Native collagen type II 40 mg + Aflapin 100 mg significantly improved joint pain, stiffness, and overall OA status by Week 4, with further gains by Week 12. No rescue medication was needed, and only mild, self-limiting AEs occurred. The combination was well tolerated and effective for knee or hip OA symptom relief.